Canine angiostrongylosis in Sweden: a nationwide seroepidemiological survey by enzyme-linked immunosorbent assays and a summary of five-year diagnostic activity (2011–2015) - Giulio Grandi (Acta Veterinaria Scandinavica, 2017)
Abstract Background For the first time in Sweden, Angiostrongylus vasorum was detected on the island of Sydkoster in foxes and dogs in 2003. After sporadic detection of the parasite in foxes in southern Sweden, the first positive canine faecal sample on the mainland was found in 2011. Since then a total of 2882 faecal samples have been analysed with the Baermann test at the National Veterinary Institute (SVA) during the years 2011–2015; 20 of them being positive. Contemporaneously, of over 525 fox necropsies, only three were found to be infected. To gather a more accurate knowledge of A. vasorum occurrence in Sweden, a large scale seroepidemiological survey was performed and totally 3885 serum samples from dogs were tested for both the presence of circulating antigens and of specific antibodies to A. vasorum. Results In total, 0.10% (n = 4, 95% Confidence Intervals, CI 0.03–0.26%) of the dogs were positive for both antigen and antibodies, whereas 0.51% (n = 20, CI 0.31–0.79%) of the tested dogs were only antigen positive and 0.88% (n = 34, CI 0.61–1.22%) only positive for specific antibodies. Seropositive animals, as well as the majority of A. vasorum-positive faecal samples tested during the same period, were spread over central and southern Sweden. Annual prevalence of positive faecal dog samples and of necropsied A. vasorum positive foxes (coming from southern Sweden) varied from 0.3 to 0.9% (overall: 0.7%, CI 0.4–1.1%) and 0.0 to 1.4% (overall: 0.3%, CI 0.1–0.9%), respectively. Conclusions The findings confirmed that A. vasorum has become established in various geographical areas of central and southern Sweden. Veterinarians and dog owners should be aware of the potential risks of infection in large areas of the country, since canine angiostrongylosis may be a fatal disease if left untreated.